Perancangan Sistem Hidrolik Mesin Press Sampah Plastik Tipe Vertikal Kapasitas 1000 Kg - Sanjaya, Antonius David; Sugiyanto, Sugiyanto; Siswantoro, Soeadgihardo; Wibowo, Setyawan Bekti (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
Waste is an ongoing environmental issue, escalating with the increasing human population on Earth. Plastic waste, commonly found in Temporary Storage Places (TPS) for waste, poses a significant concern. In the Condongcatur area, one TPS produces waste with a daily volume of 1022 m3, consisting of 52% plastic waste. The percentage of plastic waste can be calculated using the density of PET at 1.35 gr/cm3, resulting in a daily mass of approximately 717 kg. To solve this problem, a vertical hydraulic press machine with a capacity of 1000 kg has been designed. The 1000 kg capacity press machine utilizes a hydraulic cylinder with CHSG (SMC) specifications, featuring a bore diameter of 40 mm, rod diameter of 22 mm, and an 800 mm stroke. The calculated working pressure is 93 bar, necessitating a hydraulic pump with a capacity of 6.62 CC/REV, a hydraulic motor with a power capacity of 1.5 KW or 2 HP, and a full load speed of 1400 rpm. The required hydraulic tank capacity is a minimum of 8 liters, ensuring the smooth operation of the entire system. This press machine effectively compacts plastic waste, saving space, and facilitating the recycling process.